The genomic architecture of bladder exstrophy epispadias complex - Beaman, Glenda M.; Cervellione, Raimondo M.; Keene, David; Reutter, Heiko Martin; Newman, William G. (Genes, 2021)
The bladder exstrophy–epispadias complex (BEEC) is an abdominal midline malformation comprising a spectrum of congenital genitourinary abnormalities of the abdominal wall, pelvis, urinary tract, genitalia, anus, and spine. The vast majority of BEEC cases are classified as non-syndromic and the etiology of this malformation is still unknown. This review presents the current knowledge on this multifactorial disorder, including phenotypic and anatomical characterization, epidemiology, proposed developmental mechanisms, existing animal models, and implicated genetic and environmental components.
CRIS-Team Scopus Importer:2021-08-13
Keywords: BEEC; Bladder exstrophy; Cloacal exstrophy; Epispadias